Dietary cost associated with adherence to the Mediterranean diet, and its variation by socio-economic factors in the UK Fenland Study. Issue 6 (19th March 2018) - Tong, Tammy Y. N.; Imamura, Fumiaki; Monsivais, Pablo; Brage, Søren; Griffin, Simon J.; Wareham, Nicholas J.; Forouhi, Nita G.
Abstract: High cost of healthy foods could be a barrier to healthy eating. We aimed to examine the association between dietary cost and adherence to the Mediterranean diet in a non-Mediterranean country. We evaluated cross-sectional data from 12 417 adults in the UK Fenland Study. Responses to 130-item FFQ were used to calculate a Mediterranean diet score (MDS). Dietary cost was estimated by matching food consumption data with retail prices of five major supermarkets. Using multivariable-adjusted linear regression, we examined the association of MDS and individual foods with dietary cost in absolute and relative scales. Subsequently, we assessed how much the association was explained by education, income, marital status and occupation, by conducting mediation analysis and testing interaction by these variables. High compared with low MDS (top to bottom third) was associated with marginally higher cost by 5·4 % (95 % CI 4·4, 6·4) or £0·20/d (95 % CI 0·16, 0·25). Participants with high adherence had higher cost associated with the healthier components (e.g. vegetables, fruits and fish), and lower cost associated with the unhealthy components (e.g. red meat, processed meat and sweets) ( P for trend <0·001 each). In total, 20·7 % (95 % CI 14·3, 27·0) of the MDS-cost association was explained by the selected socio-economic factors, and the MDS-cost association was of greater magnitude in lower socio-economic groups ( P interaction <0·005). Overall, greater adherence to the Mediterranean diet was associated with marginally higher dietary cost, partly modified and explained by socio-economic status, but the potential economic barriers of high adherence might be offset by cost saving from reducing unhealthy food consumption.